PROOF OF CONCEPT OF MULTI-LAYERED SWITCHES CONTROLLER USING GUI - Md Noor, Ainul Syahira (Journal of Computing Technologies and Creative Content, 2019)
The purpose of this project is to develop a prototype system namely “Proof of Concept of Multi-Layered Switches Controller Using GUI”. The main purpose of developing this prototype is to help simplify configuration basically using the Command-Line Interface (CLI) method. There are some problems like many steps to do if using the CLI method. In addition, CLI is also not user-friendly and complicates the network admin or user to remember the Command-Line used to create the configuration. Basically, this prototype uses communication between computers and multilayer switch. The system also plays a role as a translator between the multilayer switching and the computer in the configuration. This prototype uses a Graphical User Interface to configure the multilayer switch. This prototype also has various show commands to see the information or configuration that has been made on the multilayer switch. This system can perform some basic configuration of the switch, such as configuration hostname, passwords, interface and protocol.